Optimization of Ion Source Head Position in the Central Region of DECY-13 Cyclotron - S Silakhuddin; I.A. Kudus (Atom Indonesia, 2017)
Optimization of the ion source head position of the DECY-13 Cyclotron in the central region has been carried out based on simulation process using a particle tracking program written in Scilab 5.2.1. The simulated particle was the H- ion that was accelerated in DECY-13 Cyclotron. The input for the program were the magnetic field and the electric field in the central region that were calculated by Opera-3D software package and TOSCA module. The optimized position of ion source head position is in a radius of 2 cm relative to the zero point of the magnet and at a distance of 4 mm relative to the puller. This result can be useful for determining the configuration of the parts in the central region when it is tested for generating the first ion beam in the future.